Obliterative bronchiolitis in rheumatoid arthritis (clinical case) - T. N. Petrachkova; I. N. Trofimenko; E. N. Dudina; A. O. Petrachkova; M. E. Kulkova (Современная ревматология, 2023)
Obliterative (constrictive) bronchiolitis (OB) is a rare disease characterized by destruction of the bronchiolar epithelium and subsequent progressive airway obstruction. OB is most common in rheumatoid arthritis (RA) compared to other systemic rheumatic diseases. Clinical manifestations of OB are found mainly with a long duration of RA and the absence of adequate therapy for articular manifestations. We present a clinical observation, demonstrating the distal respiratory tract involvement in a patient with RA during the first year of the disease, which is observed in no more than 10–20% of cases. The nonspecificity of respiratory symptoms on the background of immunosuppressive therapy led to a diverse differential diagnostic spectrum of pulmonary pathology. For timely diagnosis and optimization of therapeutic approaches, clinical suspicion for respiratory lesions in patients with RA and interdisciplinary cooperation are necessary.